Sphenoid Sinus Aplasia: A Case Report and Review of Literature - Omkar V. Shinde; Sunil S. Mishra; Omkar P. Jathar; Anupama Anand Chavan; Anita D. Munde (ENT Updates, 2024)
The paranasal sinuses are air-filled spaces which begin developing prenatally. The sphenoid sinus is a paired paranasal sinus located within the sphenoid bone’s body. It represents one of four pairs of paranasal sinuses. A sphenoid sinus septum separates the pair of sphenoid sinuses in the middle. Each sphenoid sinus connects with the nasal cavity via the sphenoidal sinus aperture. The size and shape of the two sphenoid sinuses vary and are frequently asymmetrical. The paranasal sinuses start to develop as evaginations of mucosa during the 3rd and 4th fetal months; however, they expand after birth to reach their normal size. The underdevelopment or agenesis of the paranasal sinuses is an infrequent occurrence; if found, it is more frequently in the frontal sinus and seldom concerns the sphenoid sinus. The authors thus present a case of sphenoid sinus aplasia detected incidentally on cone-beam computed tomography (CBCT) and believe it will be a valuable addition to the literature.